Ocular trauma in patients presenting to Dhulikhel Hospital - Sthapit, P R; Marasini, S; Khoju, U; Thapa, G; Nepal, B P (Kathmandu University Medical Journal, 2012)
Background Ocular trauma is an important cause of blindness and ocular morbidity throughout the world. Prevalence studies help to define the target group, plan strategies and thereby lessen trauma related blindness in the country. Objective To identify the risk factors for ocular trauma, those at risk, describe the visual acuity at time of clinical presentation, and assess the nature and severity of ocular trauma in patients presenting to Dhulikhel Hospital’s emergency department and eye OPD with ocular trauma. Methods It is a descriptive and prospective study of all the patients with ocular trauma presenting to Dhulikhel Hospital from December 2009 to December 2010. A complete history and detailed ophthalmologic evaluation was done and noted down. Results There were 112 subjects with ocular trauma. Mean age was 28.43±16.36 years with a range of one year to 74 years. Males predominated with 72.3% frequency (p<0.001). Incidence peaked in third decade of life (p<0.01). Ocular trauma peaked in months of September and October. Presenting visual acuity better than 6/12 was noted in 83.9% of cases whereas 2.7% of cases had visual acuity of <3/60. Household (56.3%, p<0.001) was the commonest place of injury with wooden objects (19.6%) being the commonest object of injury. Most of the injuries were mechanical (85.7%, p>0.001). Conclusion Blunt injuries were more common in young males. Household and workplace were common location of ocular injuries. Public awareness and strict legislation to use personal protective devices can help to reduce the occurrence of ocular injury. http://dx.doi.org/10.3126/kumj.v9i1.6264 Kathmandu Univ Med J 2011;9(1):54-7